PENGARUH PERAN APARAT PENGAWAS INTERN PEMERINTAH TERHADAP PENERAPAN GOOD GOVERNANCEDAN IMPLIKASINYA PADA KINERJA PEMERINTAH - Darmawiguna, I Made Yoga; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2017)
The effectiveness of the role of Government Internal Supervisory Apparatus (APIP) is expected to optimize the implementation of good governance so that the implications on improving government performance. The purpose of this study to provide empirical evidence of the influence of APIP role towards the implementation of good governance and the implications from the implementation good governance on government performance. The study was conducted at SKPD Denpasar City and samples were obtained by 50 SKPD with nonprobability sampling methods with saturated samples techniques. Data collected through questionnaires. Techniques of data analysis is Partial Least Square (PLS). The result finds that the role APIP positive effect on the implementation of good governance. The role APIP positive effect on government performance. Implementation of good governance positive effect on government performance. The role APIP positive effect simultaneous on the implementation of good governance and implementation of good governance on government performance. Keywords : Government Internal Supervisory Apparatus (APIP), Good Governance, Government Performance